Analisis Nuzul Al-Quran dengan Gerhana Matahari Cincin Perspektif Astronomi - Ahmad Izzuddin; Alamul Yaqin (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2019)
Historians differ in their opinion regarding the time of NuzÅ«l al-Qurâ€™Än i.e the 17th, 19th, 21st and 24th Ramadhan -12 H. The author is interested in verifying the time of NuzÅ«l al-Qurâ€™Än by tracing the events that can be read easily the time and date i.e annular solar eclipse 27th January 632 AD when the death of Ibraham's son Muhammad. The author uses new moon data of Accurate Times 5.6 month data with crescent visibility criteria of Odeh and new MABIMS and by adding the 13th month (nasÄ«') every 3 years to find out the date of the NuzÅ«l al-Qurâ€™Än event. The purposes of this research are to know the date of NuzÅ«l al-Qurâ€™Än by tracing annular solar eclipse 27th January 632 AD and to know the factors of the different date of NuzÅ«l al-Qurâ€™Än among historians. This research uses historical research methods with steps: Heuristics (Source Collection), Source Criticism, Interpretation and Historiography (Presentation of results). The results of this research are NuzÅ«l al-Qurâ€™Än occurred on Monday, 17 Ramadhan -12 H which coincided with 19 January 610 M